α-galactosylceramide-induced liver injury in mice is mediated by TNF-α but independent of Kupffer cells - Biburger, Markus; Tiegs, Gisa (Journal of Immunology, 2005)
NKT cells expressing phenotypic markers of both T and NK cells seem to be pivotal in murine models of immune-mediated liver injury, e.g., in Con A-induced hepatitis. Also α-galactosylceramide (α-GalCer), a specific ligand for invariant Vα14 NKT cells, induces hepatic injury. To improve the comprehension of NKT-cell mediated liver injury, we investigated concomitants and prerequisites of a-GalCer-induced hepatitis in mice. Liver injury induced by α-GalCer injection into C57BL/6 mice was accompanied by intrahepatic caspase-3 activity but appeared independent thereof. α-GalCer injection also induces pronounced cytokine responses, including TNF-α, IFN-γ, IL-2, IL-4, and IL-6. We provide a detailed time course for the expression of these cytokines, both in liver and plasma. Cytokine neutralization revealed that, unlike Con A-induced hepatitis, IFN-γ is not only dispensable for α-GalCer-induced hepatotoxicity but even appears to exert protective effects. In contrast, TNF-α was clearly identified as an important mediator for hepatic injury in this model that increased Fas ligand expression on NKT cells. Whereas intrahepatic Kupffer cells are known as a pivotal source for TNF-α in Con A-induced hepatitis, they were nonessential for α-GalCer-mediated hepatotoxicity. In α-GalCer-treated mice, TNF-α was produced by intrahepatic lymphocytes, in particular NKT cells. BALB/c mice were significantly less susceptible to α-GalCer-induced liver injury than C57BL/6 mice, in particular upon pretreatment with D-galactosamine, a hepatocyte-specific sensitizer to TNF-α-mediated injury. Finally, we demonstrate resemblance of murine α-GalCer-induced hepatitis to human autoimmune-like liver disorders. The particular features of this model compared with other immune-mediated hepatitis models may enhance comprehension of basic mechanisms in the etiopathogenesis of NKT cell-comprising liver disorders. Copyright © 2005 by The American Association of Immunologists, Inc.